Ukrainian research perspective in the context of stylistic discussions of the XVI International congress of slavists - Shevchenko, Larysa (Current issues of Ukrainian linguistics: theory and practice, 2019)
The article analyzes "state and status" of functional stylistics in Ukraine in the beginning of the 21st century in the categories and concepts of modern linguistics. The research context of the analysis is determined by comparison with the stylistic issues of the XVI International Congress of Slavists, held on August 20-27, 2018 in Belgrade (Serbia). Issues of synchronization of scientific consciousness with time of culture, its chronological sections, configurations of development, evolution of cultural consciousness, changes of cultural verbalized patterns and reasons for emergence of new ideas and non-standard intellectual reflection in the scientific knowledge of linguistic consciousness are being actualized. It is stated that the triad "human - science - time of culture" is dominant in linguistics, defining at the same time the peculiarities of the information age: the synthesis of humanistic tradition and new, paradoxical scientific ideas is quite representative for world linguistics, which is clearly represented in Ukrainian stylistics. The author unfolds the thesis about the formation of scientific consciousness as an existential search for the spiritual affinity of researchers. Thus, in the development of functional stylistics, one can observe continuity from F. de Saussure to the linguists of the XXI century, where the Geneva, Baden or Prague schools ideologically formed various national scientific discourses. The problematic aspects in the development of modern stylistics with their projection into Ukrainian linguistics are considered: the systematic nature of operational stylistic terminology, the diffusion of the objectivity of various areas of linguistics, in particular, functional stylistics, communicative linguistics and genomics, logics of formation of neolinguistics as a subject area that relies on synthesis of linguistic functionalism and other branches of human sciences, etc. The criteria of the Ukrainian research perspective in modern stylistics are formulated.